Blood and urinary cytokine balance and renal outcomes at orthopaedic surgery - McBride, William T.; Kurth, Mary Jo; Watt, Joanne; Irvine, Allister; Domanska, Anna; McLean, Gavin; Lamont, John V.; Fitzgerald, Peter; Ruddock, Mark W. (Frontiers in Endocrinology, 2024)
BackgroundIn patients undergoing orthopaedic trauma surgery, acute kidney injury (AKI) can develop post-operatively and is a major cause of increased mortality and hospital stay time. Development of AKI is associated with three main processes: inflammation, ischaemia-reperfusion injury (IRI) and hypoperfusion. In this study, we investigated whether ratios of urine and blood anti-inflammatory biomarkers and biomarkers of hypoperfusion, IRI and inflammation are elevated in patients who develop post-trauma orthopaedic surgery acute kidney injury (PTOS-AKI).MethodsBlood and urinary biomarkers of inflammation, hypoperfusion and IRI were analysed in 237 patients undergoing orthopaedic fracture surgery pre- and post-operatively. Biomarker ratios were compared between non-PTOS-AKI and PTOS-AKI patients.ResultsMultiple inflammatory biomarkers were significantly elevated in PTOS-AKI patients compared to non-PTOS-AKI patients. When urine anti-inflammatory biomarkers were expressed as biomarker ratios with biomarkers of inflammation, hypoperfusion and IRI, multiple ratios were lower in PTOS-AKI patients. In contrast, blood anti-inflammatory biomarkers when expressed as ratios with blood proinflammatory biomarkers were elevated in PTOS-AKI patients.DiscussionReductions in ratios of urine anti-inflammatory and proinflammatory biomarkers in PTOS-AKI patients suggest that the renal anti-inflammatory response is protective against the proinflammatory response in patients who do not develop PTOS-AKI. Detection of proinflammatory and anti-inflammatory biomarkers both pre- and post-operatively may be useful in detecting patients at risk of developing AKI after orthopaedic surgery.